Musculoskeletal Radiology Practice Subspecialization in Canada: A Subject of Substance? - Walker, Richard E. A.; Hiemstra, Laurie A.; Forster, Bruce B. (Seminars in Musculoskeletal Radiology, 2018)
Scientific and technological advances in medical imaging have had a profound impact on health care around the world including Canada. The cost of imaging, however, continues to rise along with innovation. Building a practical subspecialty musculoskeletal imaging service offers the specialty of radiology an opportunity to show how radiologists can consistently add value and improve outcomes without adding a great cost burden to the health care system.
Keywords: subspecialization; musculoskeletal radiology; value